Simultaneous Estimation Methods for Large- and Medium-size Econometric Models - Maddala, G. S. (Review of Economic Studies, 1971)
Journal Article Simultaneous Estimation Methods for Large- and Medium-size Econometric Models Get access G. S. Maddala G. S. Maddala University of Rochester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 4, October 1971, Pages 435–445, https://doi.org/10.2307/2296688 Published: 01 October 1971